Synchronising Mobile Electronic Case Report Forms with a Central Database. - MÜLLER, Thomas H. (Studies in Health Technology & Informatics, 2016)
The increased dissemination of powerful mobile computing devices with access to a variety of wireless communication channels has benefited on-line capture of medical research data many areas. Yet, there is still a need for off-line capture, especially, when the availability of on-line connectivity cannot be established in advance. The clinical study "BreathEase" presents such a case, because it calls for extensive interviews conducted at the patient's home by visiting study staff. On the other, patient data also needed to be collected in an outpatient clinic. Furthermore, these activities needed to be co-ordinated according to protocol guidelines via a stationary system. Hence, the interview questionnaire data captured off-line needed to be merged with a stationary central database. For this purpose, an existing electronic data capture system (DBFORM) was conFred to include some clinical trial management features and complemented with a module to synchronize data in the mobile and stationary databases. This paper describes the requirements, the procedure, and its implementation. While it is shown that off-line capture followed by on-line synchronization is feasible, certain ambiguities may arise that should be addressed by technical and/or other means.